Optimizing irrigation efficiency through the consideration of soil hydrological properties – examples and simulation approaches - Grashey-Jansen, Sven (ERDKUNDE, 2014)
Climate change is connected with a global increase in the use of irrigation. But irrigation is often practiced on very variable soils with the consequence of over- or under-irrigation. The efficiency of irrigation techniques is closely connected with soil hydrological and soil physical interactions in the main root zone. In irrigation practice the deciding and often site-specific soil properties are usually not taken into consideration. This paper will emphasize the importance of soil texture in terms of improving irrigation by summarizing some results of longtime studies about soil water dynamic under the influence of irrigation. Furthermore, the paper presents possibilities of optimizing irrigation on the basis of two simulation approaches. In the first simulation approach a multi-agent-based tool calculates soil specific and corresponding water tensions by using pedotransfer functions. This makes possible a quantification of the need for irrigation and the control of the irrigation system. By integrating the physical concept of soil water potentials, temporal and spatial soil water fluxes are used to schedule dynamic and precision trickle-irrigation. The second simulation approach calculates a field-irrigation with simultaneous consideration of the horizontal variability of soil properties. The irrigation is carried out in a site-specific way with high precision. Both approaches show that precision and soil specific irrigation is accompanied by a significant reduction of irrigation water and an improvement of irrigation efficiency.